Plotting the Dystopianism in Munis Arazaz’ Confessions of Silencer - Alkouri, Ahmad Mohd (Dirasat: Human and Social Sciences, 2024)
Objectives: This paper conveys a critical analysis of Munis Arazaz’ Confessions of Silencer raising significant questions on the nature of dystopia in the Arab World during the 1980s. The novel designates the upsurge of authoritarianism and how people are manipulated. Methods: The study employed the inductive and deductive methods, as well as the analytical approach, regarding the literary function of dystopia. It explored how dystopia was employed as a literary tool in the novel Confessions of Silencer, and why it became a significant structural component in it. This study provides an adequate interpretation of the concept of dystopia by gathering data and evidence from articles and books, and subsequently analyzing and applying them to the selected novel. Results: The analysis elucidated the writer’s use of techniques such as narrative suspense to respond to instances of violence in this era. It also explored techniques in which Munis Arazaz’ Confessions of Silencer can help in recognizing dystopia in the Arab regime. It specifically emphasised the reactions to dystopia and considered the status of literature as an approach to create awareness about the violence of Arab regimes. Conclusions: The conclusion maps how Arazaz employed dystopia in his Confessions of Silencer and used his literary historical imagination to deliver a comprehensible narrative. It pointed to the Arab Regimes’ exploitation and authoritarianism.